Family-Based Treatment of Early Childhood OCD: The Pediatric OCD Treatment Study Junior (POTS Jr.) Randomized Controlled Trial - Freeman, Jennifer (JAMA Psychiatry, 2014)
IMPORTANCE. Cognitive-behavioral therapy (CBT) has been established as efficacious for obsessive compulsive disorder (OCD) in older children and adolescents, yet its effect in young children has not been evaluated sufficiently. OBJECTIVE. To examine the relative efficacy of family-based CBT (FB-CBT) involving exposure plus response prevention (EX/RP) versus a family-based relaxation treatment (FB-RT) control condition for children ages 5 – 8. DESIGN, SETTING, AND PARTICIPANTS. A 14 week randomized controlled trial (RCT) conducted at three academic medical centers between 2006 and 2011, involving 127 pediatric outpatients ages 5 – 8 with a primary diagnosis of OCD and a Children’s Yale-Brown Obsessive Compulsive Scale (CY-BOCS) total score of 16 or higher. INTERVENTIONS. Participants were randomly assigned to 14 weeks of: (1) FB-CBT including exposure plus response prevention (EX/RP); or (2) FB-RT. MAIN OUTCOME MEASURES. Responder status defined as an Independent-Evaluator (IE) rated Clinical Global Impression - Improvement (CGI-I) score of 1 (very much improved) or 2 (much improved) and change in IE-rated continuous CY-BOCS total score. RESULTS. FB-CBT was superior to FB-RT on both primary outcome measures. The percentages of children who were rated as 1 (very much improved) or 2 (much improved) on the Clinical Global Impression-Improvement scale at 14 weeks were 72% for FB-CBT and 41% for FB-RT. The effect size difference between FB-CBT and FB-RT on the CGI-I was 0.31 (95% CI, 0.17 to 0.45). The number needed to treat (NNT) with FB-CBT versus FB-RT was estimated as 3.2 (95% CI, 5.8 to 2.2). The effect size difference between FB-CBT and FB-RT on the CY-BOCS at Week 14 was 0.84 (95% CI, 0.62 to 1.06). CONCLUSIONS AND RELEVANCE. A comprehensive, family based CBT program was superior to a relaxation program with similar format in reducing OCD symptoms and functional impairment in young children (ages 5-8) with OCD.